Entanglement dynamics of bipartite quantum systems. - Tee, Xian Yang. (2009)
The rapid growth of the research on quantum entanglement over the past two decades is mainly motivated by the early works of Einstein et al (EPR), Schrödinger, John Bell, and more recently by pioneers in quantum information science such as Bennett, Arket, to name a few. Whereas Einstein et al’s, Schrödinger’s, and John Bell’s works teach us that quantum entanglement is a real, non-local, and truly quintessential phenomenon of quantum mechanics which deepen our understanding of Nature at “underground level”, the works by pioneers in quantum information science such as Bennett, Akert and etc, teach us that quantum entanglement is also a highly useful physical resource, with which and some other quantum features of quantum mechanics we can develop a new generation of information technology.